Komparasi Determinan Pembiayaan Pada Bank Mandiri Dan Bank Syariah Mandiri - Lantip Susilowati; Nita Sistiani (LPPM ISNJ Bengkalis, 2021)
The purpose of this research is to show the differences in financing between Bank Mandiri and Bank Syariah Mandiri; the effect of the inflation rate on financing; the influence of the BI-7 day repo rate on financing; the influence of the number of third party funds on financing; the effect of the statutory reserve requirement on financing. This research uses a quantitative approach with associative and comparative types of research. The sampling technique used was the purposive sampling method. The test uses a hypothesis test and an independent sample test to compare the financial performance of the two banks. The results showed that the inflation rate, BI-7 day repo rate, and the minimum reserve requirement had no effect on financing at Bank Mandiri and Bank Syariah Mandiri. While third-party funds partially have a positive and significant effect on financing at Bank Mandiri and Bank Syariah Mandiri. There is a significant difference between financing between Bank Mandiri and Bank Syariah Mandiri. This research can provide input for Islamic banking, especially Bank Mandiri and Bank Syariah Mandiri, in determining profit-sharing financing policies.